MORC Domain Definition and Evolutionary Analysis of the MORC Gene Family in Green Plants. (2nd July 2018) - Dong, Wei; Vannozzi, Alessandro; Chen, Fei; Hu, Yue; Chen, Zihua; Zhang, Liangsheng
Abstract: Microrchidia (MORC) proteins have been described as epigenetic regulators and plant immune mediators in Arabidopsis . Typically, plant and animal MORC proteins contain a hallmark GHKL-type (Gyrase, Hsp90, Histidine kinase, MutL) ATPase domain in their N-terminus. Here, 356 and 83 MORC orthologues were identified in 60 plant and 27 animal genomes. Large-scale MORC sequence analyses revealed the presence of a highly conserved motif composition that defined as the MORC domain. The MORC domain was present in both plants and animals, indicating that it originated in the common ancestor before the divergence of plants and animals. Phylogenetic analyses showed that MORC genes in both plant and animal lineages were clearly classified into two major groups, named Plants-Group I, Plants-Group II and Animals-Group I, Animals-Group II, respectively. Further analyses of MORC genes in green plants uncovered that Group I can be subdivided into Group I-1 and Group I-2. Group I-1 only contains seed plant genes, suggesting that Group I-1 and I-2 divergence occurred at least before the emergence of spermatophytes. Group I-2 and Group II have undergone several gene duplications, resulting in the expansion of MORC gene family in angiosperms. Additionally, MORC gene expression analyses in Arabidopsis, soybean, and rice revealed a higher expression level in reproductive tissues compared with other organs, and showed divergent expression patterns for several paralogous gene pairs. Our studies offered new insights into the origins, phylogenetic relationships, and expressional patterns of MORC family members in green plants, which would help to further reveal their functions as plant epigenetic regulators.